The use of solenoidal winding models for the calculation of the leakage inductance of power transformers - Маслюченко, Игорь Николаевич (Technology audit and production reserves, 2015)
The necessity of modification of the known method of average distances for calculating leakage inductance of power transformer windings. The calculated expressions for the leakage inductance of power transformers obtained from the use of solenoidal winding models are given. Theoretical materials of the article tested on the results of the experiment. A calculation expression of leakage inductance with the relative sizes of the windings is proposed. The relevance of this article due to the absence, to date, the recommendations for engineering calculations the leakage inductance of power transformer windings, based on the use pattern of the magnetic field of windings with the saturation of steel of magnetic core. As a result it is shown that multiple attempts to develop a method of average geometric distances with rectangular cross-sections of the windings can be successfully replaced the use of solenoidal models. For the first time it is obtained an experimental confirmation of the proposed modification of the method of average geometric distances. On the basis of article materials can be constructed rapid calculation methodology of leakage inductance of power transformer windings for their design, as well as testing.